ISLAMIC PSYCHOTHERAPY IN THE PANDEMIC OF COVID-19 - Ilyas, Sabrida Muhammad (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2020)
When God sent disaster in the form of the disease in humans in the world, God also gave instructions on how to deal with and treat it in His book. This paper explains the spiritual values and religiosity through Islamic psychotherapy whose aim is to provide a religious / Islamic nuanced solution to the problem of anxiety disorders and contracting Covid-19 that engulfs the world. The method that I use in this paper is a descriptive analysis method, in which the author presents data from several relevant opinions and tested through various sources then analyzes it, to produce a more effective alternative that is packaged in an appropriate, actual, factual, and contextual method. One approach to dealing with the problem of anxiety disorders and exposure to Covid-19 during a pandemic is through therapy. Sufism patience therapy seeks to optimize and unleash human spiritual energy through three phases. The takhalli phase is the phase in which humans cleanse impurities both physically and the heart, the tahalli phase is where humans learn to decorate themselves or behave with commendable qualities and the tajalli phase is how humans feel a good relationship with God is established. Patience therapy with verses of the Koran specifically to cure all diseases, namely: Quran in Surah Al-Isra 'verses 82, Surah Al-Anbiya verses 83-84, and Surah Al-Fatihah verses 1-7.